INSTABLE (Integrated Stock Raising Double Solution) Application Intergrated Farming System Zero Waste by Black Soldier Fly Larvae Cultivation, Organic Composter Process and Feed Processing for Islamic boarding school Raudhatul Madinah Batu - nurul - rodiyah (Journal of Innovation and Applied Technology, 2019)
Agriculture is a vital sector as a provider of community food. The use of natural resources in Indonesia is still less effective. The purpose of this research is to apply integrated farming system to improve the effectiveness of natural resource management. The result of devotion shows the real effect between the application of integrated farming system through the making of compost from the feces, the making of silage from the vegetable waste, the planting of vegetables from compost, the cultivation of maggot and its utilization as fish feed and poultry. Implementation of integrated agricultural system will increase revenue because it reduces the percentage of inputs of goods from outside the scope of cultivated land. Integrated farming system INSTABLE is expected to be able to make student excellence as human resource manager of agriculture.